Design and performance analysis of a twin T-bridge RC harmonic oscillation generator with an operational amplifier - Boyan Karapenev (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
This paper presents the special features of harmonic generators and their widespread use and in particular the design, simulation and experimental studies of a twin T-bridge RC generator with an operational amplifier. The results obtained are analyzed and compared. For the particular implementation, the frequency error varies from 4 % in experimental studies to 6.7 % in the simulation, and in this case an average value of 5.35 % can be assumed.